Survey of biodegrading agents in logs and planks in selected sawmills and timber markets in Ibadan Oyo State (2015)
Biological deterioration of wood is one of the major challenges on wood utilization especially in tropical countries like Nigeria. This is because of the favourable weather condition for the bin-deteriorating agents to thrive. This study is therefore carried out to investigate the biodegrading agents of logs in sawmills and planks in plank markets in Ibadan, Nigeria. Data for the study were collected using checklist, and laboratory examination of collected samples from decayed logs and planks. The data obtained were subjected to descriptive statistics. The results of the laboratory examination revealed that a variety of fungi moulds, namely Aspergillus flavus Fredrick Link, Aspergillus niger VanTieghem, Botryodiplodia theobromae Pat, Trichodermalongi brachlatum Rifai, Penicillium oxalicum Currie and Thorn, Rhizopus stolonifer,(Ehrenb.ex Fr)., that are not host specific were encountered. Botryodiplodia theobromae Pat, was present in all the three sawmills and two timber markets while Aspergillus flavus Fredrick Link and Aspergillus niger VanTieghem, were present in only one sawmill (Moniya). The order Coleoptera and Isoptera were the two prominent insect pest groups identified. These were from seven families out of which five species of insects namely Termites, Beetles, Borers, Weevils and Carpenter ants were identified. The degree of molds growth on the surface of the wood is an indication that the conditions are favourable for wood decay to occur. It is therefore recommended that logs should be properly handled during log storage and processing in the mills by keeping the environment clean. Processed timbers should also be arranged in such a way that there will be free flow of air within stacked timber.